Determining the effects of standardized ileal digestible tryptophan:lysine ratio and tryptophan source in diets containing dried distillers grains with solubles on growth performance and carcass characteristics of finishing pigs - Nitikanchana, S.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 2,290 pigs (PIC 1050 × 337; initially 157 lb) were used to determine the effect of tryptophan source (L-tryptophan vs. soybean meal) and increasing SID tryptophan:lysine ratio in diets containing 30% dried distillers grains with solubles (DDGS) on finishing pig performance. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 7 dietary treatments in a completely randomized design with 26 to 28 pigs per pen and 10 to 13 replications per treatment. Treatments were arranged as a 2 × 3 factorial with main effects of tryptophan source (L-tryptophan or soybean meal) and SID tryptophan:lysine ratio (18, 20, and 22% of lysine). The seventh treatment was a negative control diet formulated to a 16% SID tryptophan:lysine ratio.
Keywords: Swine; Amino acids; DDGS; Finishing pig; Lysine; Tryptophan